Professional Competences of Jurisprudence Educators - Гусенко, Анжела Анатоліївна; Гусенко, А. А.; Гусенко, Анжела Анатольевна; Husenko, Anzhela A.; Петруненко, Ярослав Вікторович; Петруненко, Я. В.; Петруненко, Ярослав Викторович; Petrunenko, Yaroslav V.; Petrunenko, Iaroslav V.; Кулініч, Ольга Олексіївна; Кулініч, О. О.; Кулинич, Ольга Алексеевна; et al. (Sciedu Press, 2020)
Nowadays, the profession of Jurisprudence educator is one of the most relevant and top requested among all specializations; however, in order to become a high-skilled Jurisprudence educator, one should possess significant professional qualities, including being professionally competent in the context of teaching. Taking into consideration the above mentioned, as well as based on the subject matter of the scientific article, the purpose of the study is to reveal the theoretical and practical features of the professional competences’formation and development of the Jurisprudence educators. Methods of analysis, synthesis, observation, description, comparison and generalization have been applied to reveal the purpose of the scientific research. It has been established that modern Jurisprudence teachers should possess the following professional competences: to be fluent in modern legislation and other legal norms; to rely on the features and qualities of leading scientists, working in this field; to be able to interconnect private and public interests and allocate responsibility to individual cases; to be well-versed in legislative practice and to act by law in unexpected situations; to encourage students to actively participate in the learning process, while avoiding delays in classes or even truancies; to expect knowledge from their studentsin a positive light; to enlist the respect and trust of students; to treat students positively and with respect, regardless of their religious, cultural, social or linguistic background; to cooperate with parents and other students’ custodial persons; to think critically and professionally; to prepare for classesto a full extent, using modern innovative teaching methods to teach material in the classroom;to take an active part in activities organized by the tertiary educational institution, local community, etc.; to be engaged in professional development, constantly improve one’s own competences. Based on the results of the conducted study of the theoretical and practical features of the professional competences’ formation and development of Jurisprudence educators it has been established that these competences begin to form and develop even at the stage, when students (future Jurisprudence educators) study at the tertiary legal educational institutions.

В наш час професія викладача з правознавства є однією з найбільш актуальних та найпопулярніших серед усіх спеціалізацій; однак, щоб стати висококваліфікованим викладачем з правознавства, слід володіти значними професійними якостями, включаючи професійну компетентність у контексті викладання. Беручи до уваги вищезазначене, а також виходячи з предмету наукової статті, метою дослідження є розкрити теоретичні та практичні особливості формування професійних компетентностей та розвитку викладачів з правознавства. Для досягнення мети наукового дослідження застосовано методи аналізу, синтезу, спостереження, опису, порівняння та узагальнення. Встановлено, що сучасні викладачі з правознавства повинні володіти такими професійними компетенціями: вільно володіти сучасним законодавством та іншими правовими нормами; спиратися на особливості та якості провідних учених, що працюють у цій галузі; мати можливість взаємопов’язати приватні та державні інтереси та розподялити зобов'язання; добре знати законодавчу практику та діяти згідно із законом у несподіваних ситуаціях; заохочувати студентів до активної участі в навчальному процесі, уникаючи затримок у заняттях і навіть прогулів; чекати знань від своїх учнів у позитивному світлі; заручитися повагою та довірою учнів; ставитися до учнів позитивно та з повагою, незалежно від їх релігійного, культурного, соціального чи мовного походження; співпрацювати з батьками та особами, які є опікунами інших учнів; мислити критично та професійно; повністю підготуватися до заняття, використовуючи сучасні інноваційні методи навчання для викладання матеріалу; брати активну участь у заходах, організованих закладом вищої освіти, місцевою громадою тощо; займатися професійним розвитком, постійно вдосконалювати власні компетенції. За результатами проведеного дослідження теоретичних та практичних особливостей формування та розвитку професійних компетентностей викладачів правознавства встановлено, що ці компетентності починають формуватися та розвиватися ще на етапі, коли студенти (майбутні викладачі правознавства) навчаються у вищих юридичних навчальних закладах.

В наше время профессия преподавателя по правоведению является одной из наиболее актуальных и популярных среди всех специализаций; однако, чтобы стать высококвалифицированным преподавателем по правоведению, следует обладать значительными профессиональными качествами, включая профессиональную компетентность в контексте преподавания. Принимая во внимание вышесказанное, а также исходя из предмета научной статьи, целью исследования является раскрыть теоретические и практические особенности формирования профессиональных компетенций и развития преподавателей по правоведению. Для установления цели научного исследования применены методы анализа, синтеза, наблюдения, описания, сравнения и обобщения. Установлено, что современные преподаватели по правоведению должны обладать такими профессиональными компетенциями: свободно владеть современным законодательством и иными правовыми нормами; опираться на особенности и качества ведущих ученых, работающих в этой области; иметь возможность находить взаимосвязь между частными и государственными интересами, распределять обязанности; хорошо знать законодательную практику и действовать в соответствии с законом в неожиданных ситуациях; поощрять студентов к активному участию в учебном процессе, избегая задержек в занятиях и даже прогулов; ждать знаний от своих учеников в положительном свете; заручиться уважением и доверием учащихся; относиться к ученикам положительно и с уважением, независимо от их религиозного, культурного, социального или языкового происхождения; сотрудничать с родителями и лицами, которые являются опекунами других учащихся; мыслить критически и профессионально; полностью готовиться к занятию, используя современные инновационные методы обучения для преподавания материала; активно участвовать в мероприятиях, организованных высшим учебным заведением, органами местной власти и т. д.; заниматься профессиональным развитием, постоянно совершенствовать собственные компетенции. По результатам проведенного исследования теоретических и практических особенностей формирования и развития профессиональных компетенций преподавателей права установлено, что эти компетентности начинают формироваться и развиваться еще на этапе, когда студенты (будущие преподаватели правоведения) учатся в высших юридических учебных заведениях.
Husenko А. А. Professional Competences of Jurisprudence Educators / A. A. Husenko , I. V. Petrunenko , O. O. Kulinich , L. V. Tokar, V. V. Herashchenko // International Journal of Higher Education. – V. 9 (7). – Sciedu Press, 2020. – Р. 345-355.
Keywords: professional competences; legal education; educator; tertiary educational institutions; jurisprudence; професійні компетенції; юридична освіта; викладач; заклади вищої освіти; юриспруденція; профессиональные компетенции; юридическое образование; преподаватель; высшие учебные заведения; юриспруденция; Research Subject Categories::LAW/JURISPRUDENCE; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education